The method of CAD model creation of dental shape based on 3D-CT images in orthodontics - Wei Ying; Tian Bao-yu; Xia Yun-ye (International Conference on Advanced Technology of Design and Manufacture (ATDM 2010), 2010)
The key difficulty of orthodontics based on CAD/CAM is how to obtain the dense, complete and ordered point cloud data of teeth. A method of obtaining the CAD model of dental shape rapidly based on 3D-CT(Three Dimensional Computed Tomography) is introduced. Firstly, the dental plaster model is scanned in 3D-CT systems and the precise gray images are obtained. The method about extracting the internal and external contour of the CT images is proposed, and some relative techniques are studied in detail during thinning and tracing the contour. In order to improve the accuracy of the contour coordinates, the moment-based contour tracing algorithm is introduced, and the sub-pixel accuracy is reached. Finally, the point cloud data are input to CAD platform to design the CAD model of the physical prototype. Compare with traditional RE(Reverse Engineering) method, this method has the virtue of fast speed, same resolution in each dimension and high accuracy.